Symmetrische Präskription in germanischen Verwandtschaftsterminologien - Pfeffer, Georg (Sociologus, 1985)
Individual Germanic kin terms, as elaborated by scholars of historical linguistics, are seen as a whole relationship system, or as an example of a particular mode of classification. Following the method developed in Dumont's analysis of the "Dravidian" system (1953), the terminology is viewed as a categorical document of necessary exchange. The "northern" (Netherlandish and Nethergerman) systems prescribe symmetric exchange between two lines while those of the southern Germanic lands combine four lines in an alternating rhythm. Thus systems of affinal prescription or expressions of analogical classification are associated with the native culture of central Europe in the same manner, as they have been with those of the well-known Oceanic, Indian or American examples.
Gesehen am 07.10.2024